IMPLEMENTASI FINTECH (E-WALLET) DALAM MENGEMBANGKAN BISNIS BAGI PELAKU UMKM DI KOTA MAKASSAR - Nurina Saffanah; Wanda Amir (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2022)
The existence of a digital wallet can improve services in the financial sector, making it easier for consumers to make transactions. In addition, the use of digital wallets by SMEs actors can be a place to promote their products through attractive promo offers on a regular basis, also help SMEs players get an investment opportunity in the digital industry and can be one of the pillars of Indonesia's economic resilience in the future. This study aims to explore the extent of the application of fintech in the form of a digital wallet for SMEs actors in Makassar. The research method used is a quantitative method with a descriptive approach to explain the purpose of the research. The data used in this study is primary data. Where data is collected through the process of filling out questionnaires distributed to SMEs actors in Makassar City. The results of this study indicate that SMEs actors have a positive perception of using digital wallets as an alternative easy payment method, reducing physical contact, increasing sales, as a product promotion event, and reducing operational costs and capital costs.